Haciéndose maestras : problemas de enseñanza en su primer y tercer año de trabajo de las maestras de educación infantil - Fandiño, Graciela (Colección Memorias y entramados educativos y culturales, 2014)
The study focuses on the problems of teaching new teachers, those beginning their professional work, once they have completed their training at the university. The study was conducted from the perspective of teacher socialization, where four levels of problems are considered: personal, social, educational and institutional.